Oxidative Stress and Cardiac Remodeling: An Updated Edge - Rababa'h, Abeer M.; Guillory, Ashley N.; Mustafa, Rima; Hijjawi, Tamara (Current Cardiology Reviews, 2018)
Background: A common phenotype associated with heart failure is the development of cardiac hypertrophy. Cardiac hypertrophy occurs in response to stress, such as hypertension, coronary vascular disease, or myocardial infarction. The most critical pathophysiological conditions involved may include dilated hypertrophy, fibrosis and contractile malfunction. The intricate pathophysiological mechanisms of cardiac hypertrophy have been the core of several scientific studies, which may help in opening a new avenue in preventive and curative procedures. Objectives: To our knowledge from the literature, the development of cardiac remodeling and hypertrophy is multifactorial. Thus, in this review, we will focus and summarize the potential role of oxidative stress in cardiac hypertrophy development. Conclusion: Oxidative stress is considered a major stimulant for the signal transduction in cardiac cells pathological conditions, including inflammatory cytokines, and MAP kinase. The understanding of the pathophysiological mechanisms which are involved in cardiac hypertrophy and remodeling process is crucial for the development of new therapeutic plans, especially that the mortality rates related to cardiac remodeling/dysfunction remain high.
Keywords: NAPDH